From: archive F. Domela Nieuwenhuis, VI a 1 B, nr 7. With dedication by Key to F. Domela Nieuwenhuis, dated May 17, 1905, on front
From: archive F. Domela Nieuwenhuis, VI a 1 B, nr 7. With dedication by Key to F. Domela Nieuwenhuis, dated May 17, 1905, on front.